Something in the wind: the influence of wind speed and direction on African lion movement behavior. (15th September 2022) - Wijers, Matthew; Trethowan, Paul; du Preez, Byron; Loveridge, Andrew J; Markham, Andrew; Macdonald, David W; Montgomery, Robert A
Abstract: Olfaction is a key sense, enabling animals to locate forage, select mates, navigate their environment, and avoid predation. Wind is an important abiotic factor that modulates the strength of olfactory information detected by animals. In theory, when airflow is unidirectional, an animal can increase odor detection probability and maximize the amount of olfactory information gained by moving crosswind. Given energetic costs inherent to activity and locomotion, behavioral search strategies that optimize the benefit-cost ratio should be advantageous. We tested whether African lions ( Panthera leo ) modify their movement directionality and distance according to wind speed and direction during hours of darkness when they are most active. We tracked 29 lions in southern Zimbabwe using GPS collars and deployed a weather station to collect detailed abiotic data. We found that when wind speeds increased lions were more likely to move crosswind. We also found that female lions, which tend to hunt more often than males, traveled farther when wind speeds were stronger. The results of our analysis suggest that lions adjust their movement behavior according to wind speed and direction. We inferred that this was a behavioral decision to maximize the amount of olfactory information gained per unit of energy spent. Our findings not only offer one of the first detailed insights on large carnivore anemotaxis (movement direction relative to wind) but also make an important contribution towards understanding the influence of wind on predator ecology in general which remains understudied to date. Abstract : An animal that moves crosswind has a better chance of detecting important scent cues in its surrounding environment such as the smell of food or mates. Modifying search behavior in response to wind speed and direction would therefore be advantageous. In African lions both males and females are more likely to move crosswind with increasing wind speed. Female lions, which tend to hunt more often than males, also travel farther in stronger winds.